Efficient Trapping of Trace Acetylene from Ethylene in an Ultramicroporous Metal–Organic Framework: Synergistic Effect of High‐Density Open Metal and Electronegative Sites. (26th August 2020) - Zhang, Zhaoqiang; Peh, Shing Bo; Wang, Yuxiang; Kang, Chengjun; Fan, Weidong; Zhao, Dan
Abstract: Acetylene (C2 H2 ) removal from ethylene (C2 H4 ) is a crucial step in the production of polymer‐grade C2 H4 but remains a daunting challenge because of the similar physicochemical properties of C2 H2 and C2 H4 . Currently energy‐intensive cryogenic distillation processes are used to separate the two gases industrially. A robust ultramicroporous metal–organic framework (MOF), Ni3 (pzdc)2 (7 Hade)2, is reported for efficient C2 H2 /C2 H4 separation. The MOF comprises hydrogen‐bonded linked one‐dimensional (1D) chains, and features high‐density open metal sites (2.7 nm −3 ) and electronegative oxygen and nitrogen sites arranged on the pore surface as cooperative binding sites. Theoretical calculations, in situ powder X‐ray diffraction and Fourier‐transform infrared spectroscopy revealed a synergistic adsorption mechanism. The MOF possesses S‐shaped 1D pore channels that efficiently trap trace C2 H2 at 0.01 bar with a high C2 H2 uptake of 60.6 cm 3  cm −3 and C2 H2 /C2 H4 selectivity. Abstract : Trace acetylene can be efficiently separated from ethylene via the synergistic effect of high‐density open metal and electronegative sites in an ultramicroporous metal–organic framework (MOF). The specific binding sites in the MOF afford an excellent acetylene uptake at 0.01 bar by maximizing the host–guest interactions.